2013
DOI: 10.1021/jo400598p
|View full text |Cite
|
Sign up to set email alerts
|

A Predictably Selective Nitration of Olefin with Fe(NO3)3 and TEMPO

Abstract: Ferric nitrate with catalytic TEMPO has been identified as a useful reagent for regio- and stereoselective nitration of a wide variety of aromatic, aliphatic, and heteroaromatic olefins. This reaction provided nitroolefins in preparatively useful yields with excellent E-selectivity. Due to its mild nature and operational simplicity, the present protocol is expected to find application in synthetic setup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 29 publications
(20 reference statements)
1
47
0
Order By: Relevance
“…Runs 1–3 showed that Fe(NO 3 ) 3 ⋅ 9H 2 O is an effective reagent for the nitration of pyrazolin‐5‐one 1 a at 60–80 °C, but at room temperature 4‐nitropyrazolin‐5‐one 2 a was obtained in a yield of only 33 % (run 4). Apparently, an elevated temperature was necessary for the decomposition of Fe(NO 3 ) 3 ⋅ 9H 2 O and the release of the active nitrating agent NO 2 . The introduction of NaNO 2 into the reaction allowed the room‐temperature nitration of pyrazolin‐5‐one 1 a in high yields (runs 5–7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Runs 1–3 showed that Fe(NO 3 ) 3 ⋅ 9H 2 O is an effective reagent for the nitration of pyrazolin‐5‐one 1 a at 60–80 °C, but at room temperature 4‐nitropyrazolin‐5‐one 2 a was obtained in a yield of only 33 % (run 4). Apparently, an elevated temperature was necessary for the decomposition of Fe(NO 3 ) 3 ⋅ 9H 2 O and the release of the active nitrating agent NO 2 . The introduction of NaNO 2 into the reaction allowed the room‐temperature nitration of pyrazolin‐5‐one 1 a in high yields (runs 5–7).…”
Section: Resultsmentioning
confidence: 99%
“…A possible reason is the interaction of the solvents and H 2 O with NO 2 , the plausible nitrating reagent generated in situ. In the nonpolar solvent C 2 H 4 Cl 2 , which has previously been widely used in nitration reactions with Fe(NO 3 ) 3 ⋅ 9H 2 O, compound 2 a was obtained in low yield (33 %, run 11), which can be explained by the low solubility of the reagents in this solvent at room temperature. In a number of studies on Fe(NO 3 ) 3 ⋅ 9H 2 O‐mediated nitration, TEMPO proved to be an effective additive to increase the yields of nitro derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 A broader range of substrates such as aliphatic, aromatic, heteroaromatic olefins can undergo this reaction in excellent yields. 32 A broader range of substrates such as aliphatic, aromatic, heteroaromatic olefins can undergo this reaction in excellent yields.…”
Section: Nitration Of Olefins C-h Bondsmentioning
confidence: 99%
“…Recently, Maiti and co-workers reported the preparation of (E)-nitroolefins from nitration of olefins using AgNO 2 /TEMPO, 7 t-BuONO/TEMPO, 8 and Fe(NO 3 ) 3 /TEMPO. 9 These methods while offering significant improvements in direct nitration of olefins have problematic issues, which include metal reagent employed, absence of recovery and reuse of the catalyst.…”
mentioning
confidence: 99%